The Effect of Drill Method Learning on Prayer Movement Skills Class III Students at SDN 20 Sitiung: Pengaruh Pembelajaran Metode Drill terhadap Keterampilan Gerak Sholat Peserta Didik Kelas III di SDN 20 Sitiung - Dharma Andika (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2021)
Prayer movement skills are the core learning material of one of the processes of Islamic religious education. The ability of students to receive learning to carry out prayer movements must be conveyed using the right method. This study discusses the effect of learning the drill method on students' prayer movement skills. In sampling the researchers used the type and research design of non-equivalent control group design with data collection before and after being given treatment. Respondents were divided into 2 groups consisting of 1 experimental group and 1 control group with a total of 50 third grade students at SDN 20 Sitiung. This research was conducted in September 2021 in the 2021/2022 Academic Year at SDN 20 Sitiung, Dharmasraya Regency. Based on the results of the study, it was found that in the experimental group, there were 23 students (92%) skilled and in the control group, 17 students (68%) were skilled and based on the comparison, there was a P-Value value of 0.002 < 0.005 which means that there is an effect of learning the drill method on the prayer movement skills of students.